Analysis of obstetrics hysterectomy in tertiary care centre - Ahirwar, Neetu; Wadhwani, Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Emergency peripartum hysterectomy (EPH) is an uncommon obstetric procedure, usually performed as a life-saving measure in cases of intractable obstetric hemorrhage. Obstetrics hysterectomy is performed on gravid uterus during pregnancy labor puerperium. It is a catastrophic inevitable lifesaving emergency procedure in cases of rupture uterus, uncontrollable post-partum haemorrhage, morbidly adherent placenta, and some cases of trauma, sever infection of pregnant uterus. Newer drug like prostaglandins, antibiotics and blood transfusion has brought down the incidence of obstetric hysterectomy. Methods: This retrospective study is performed in department of obstetrics and gynaecology SZH Gandhi medical college Bhopal. Retrospective analysis of record done. Results: In this study there were 51867 deliveries and 99 0bstetric hysterectomy giving the incidence as 1 in 524 deliveries. There were 17113 cesarean section performed hence the incidence as 1 in 173 cesaren section. Majority of patient belong to group para 4 and above i.e. 32.32%. Least incidence is among nullipara patient i.e. 2.02%. The most common indication of obstetric hysterectomy in this study was morbidly adherent placenta, 52 cases i.e. 52.52%% Rupture uterus was second common indication accounting for 36.36% of cases. Most common additional surgical procedure done during obstetric hysterectomy was repair of bladder tear and salpingoophrectomy done in 7 cases i.e. 7.07% of each. Repair of bowel injury done in 1 case i.e. 1.01%. Conclusions: Incidence of maternal mortality in cases of obstetric hysterectomy was 9.09%. most common cause of maternal mortality was haemorrhagic shock accounting for 55.55.